ANALISIS KETERBATASAN SARANA DAN PRASARANA DALAM FAKTOR PENDUKUNG PRESTASI KLUB BOLA VOLI VILLOR - Cahyati, Nurnisa; Huda, Benijar Pahrul; Munabil, Muhamad Rofiq; Rahman, Aam Ali; Suherman, Ayi (STKIP Melawi, 2025)
Abstract: This study aims to analyze the limitations of facilities and infrastructure as supporting factors for the achievements of the Villor Volleyball Club in Cimanggung District, Sumedang Regency. The study used a qualitative descriptive method with a case study approach, involving coaches, administrators, and club athletes. The results of the study showed that although the facilities and infrastructure were inadequate, support from the community, family, and club management contributed significantly to the club's success. External factors such as family support (69.17%) and the community (71.17%) were the main drivers, while internal factors such as the physical condition of athletes (73.33%) also played an important role. This study recommends improving facility management, collaborating with the government and sponsors, and optimizing existing facilities to support athlete achievements sustainably.Keywords: volleyball, facilities and infrastructure, athlete achievements, supporting factorsÂ Â Abstrak: Penelitian ini bertujuan untuk menganalisis keterbatasan sarana dan prasarana sebagai faktor pendukung prestasi Klub Bola Voli Villor di Kecamatan Cimanggung, Kabupaten Sumedang. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus, melibatkan pelatih, pengurus, dan atlet klub. Hasil penelitian menunjukkan bahwa meskipun sarana dan prasarana kurang memadai, dukungan masyarakat, keluarga, serta manajemen klub memberikan kontribusi signifikan terhadap keberhasilan klub. Faktor eksternal seperti dukungan keluarga (69,17%) dan masyarakat (71,17%) menjadi penggerak utama, sementara faktor internal seperti kondisi jasmani atlet (73,33%) juga memainkan peran penting. Penelitian ini merekomendasikan peningkatan manajemen fasilitas, kolaborasi dengan pemerintah dan sponsor, serta optimalisasi fasilitas yang ada untuk mendukung prestasi atlet secara berkelanjutan.Kata Kunci: bola voli, sarana dan prasarana, prestasi atlet, faktor pendukung